Disaster Risk Reduction and Emergency Management in Armenia - Global Facility for Disaster Reduction and Recovery (World Bank, Washington, DC, 2017)
This report addresses the fact that natural disasters have caused vast social upheaval and economic damage to Armenia. This ongoing vulnerability to natural disasters has led Armenia to appreciate the advantages of developing a comprehensive strategy to help minimize ensuing fiscal exposure because the national budget will never be adequate to mitigate, respond, and recover from these recurrent but unavoidable crises. Since the Spitak earthquake, Government has reorganized its emergency management system and established many seismic mitigation activities and created a Ministry of Emergency Situations (MoES) and established a cabinet-level Minister responsible for disaster response. Government may wish to build on these achievements. The report is also based on a study carried out in Armenia under the Global Facility for Disaster Reduction and Recovery (GFDRR) project, which analyzed disaster risks, assessed existing systems, mechanisms, and institutional capacities, and made recommendations for developing a comprehensive national disaster reduction and preparedness agenda, which could form the basis for a natural disaster reduction project.